Defekty predsienového septa: význam peroperacného morfometrického hodnotenia defektov - Siman, J; Simkovic, I; Vrsanský, D; Hraska, V; Outrata, R; Slezák, J (Rozhledy v chirurgii, 1989)
The authors analyze the results of preoperative morphometry of atrial septal defects. They compare the area of the defect and the septal area in different types of defects. Based on the thus obtained relative value, they select either suture of the defect or its correction by means of a patch. They emphasize that during correction defects deformations and reduction of the septal area must be avoided. They do not admit the possibility that the suture of the defect is exposed to traction. Ostium secundum defects the area of which is greater than 40% of the septal area are suited for correction by means of a patch. An important indicator is the transverse dimension of the defect and of the septum. This relation determines the grade of deformity during an inadequately selected suture and the presence of traction mechanisms in the area of the suture and cardiac skeleton. The authors recommend more frequent use of patches also in ostium secundum defects in the cranial lateral and distal part of the atrial defect.
Keywords: kojenec; Infant; mladiství; Child; Infant, Newborn; novorozenec; předškolní dítě; dítě; Child, Preschool; lidé; Heart Septal Defects, Atrial; defekty septa síní; Humans; Adolescent